2011
DOI: 10.1242/jeb.057133
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue-related adaptations in muscle coordination during a cyclic exercise in humans

Abstract: SUMMARYMuscle fatigue is an exercise-induced reduction in the capability of a muscle to generate force. A possible strategy to counteract the effects of fatigue is to modify muscle coordination. We designed this study to quantify the effect of fatigue on muscle coordination during a cyclic exercise involving numerous muscles. Nine human subjects were tested during a constant-load rowing exercise (mean power output: 217.9±32.4W) performed until task failure. The forces exerted at the handle and the footstretch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 52 publications
3
30
2
Order By: Relevance
“…Additionally, our intervention was not a fatigue protocol. Thus, our data was different from those obtained by Turpin et al29 ) .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Additionally, our intervention was not a fatigue protocol. Thus, our data was different from those obtained by Turpin et al29 ) .…”
Section: Discussioncontrasting
confidence: 99%
“…Turpin et al29 ) reported that there was no change for the modules due to muscle fatigue during rowing exercise although our results showed a couple of different modules. Rowing exercise is performed in a stable condition in the sitting position.…”
Section: Discussioncontrasting
confidence: 66%
“…EMG signals were band-pass filtered (20–450 Hz, Butterworth filter, 2nd order), rectified, smoothed with a zero lag low-pass filter (9 Hz, Butterworth filter, 2nd order), and time-normalized in order to obtain 200 data points for each giant swing. EMG was normalized to the maximum level of activity across all giant swings (Turpin et al, 2011a). Therefore, as is classically done in studies focusing on muscle synergies, the degree of muscle activity was not taken into consideration.…”
Section: Methodsmentioning
confidence: 99%
“…These factors determine external and internal conditions of realization of athletes' motor potential in the process of competition activity [13,27]. Winners of elite competitions in kinds of sports for endurance do not reduce speed at the end of distance but increase it in state of rising fatigue [29]. With it, technique of main sport movement changes [4,18].…”
Section: Introductionmentioning
confidence: 99%